2007
DOI: 10.1021/ja0701208
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Growth of the Metal Organic Framework Cu3(BTC)2(H2O)3·xH2O Tunable with Functionalized Self-Assembled Monolayers

Abstract: The tunable oriented growth of thin films of the porous framework HKUST-1 (Cu3(C9H3O6)2(H2O)3·xH2O) on different functionalized self-assembled monolayers (SAMs) is demonstrated. Films grown on carboxylate-terminated self-assembled monolayers are highly oriented along the [100] direction, while alcohol-terminated surfaces induce a completely different orientation along the [111] direction. Homogeneous but less oriented thin films are also obtained on methyl-terminated SAMs. A combination of X-ray diffraction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
430
2
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 513 publications
(487 citation statements)
references
References 21 publications
23
430
2
13
Order By: Relevance
“…The solvent is composed of water (4 mL) -ethanol (2 mL) -DMF (1 mL). In this study, in accord with previous works, all the diffraction peaks matched exactly with the pure Cu-BTC, [29][30][31][32] and no additional peak of impurities was detected. The result of the XRD patterns suggests that pure Cu-BTC can be synthesized by sonochemical method within 1 min at room temperature and atmospheric pressure.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The solvent is composed of water (4 mL) -ethanol (2 mL) -DMF (1 mL). In this study, in accord with previous works, all the diffraction peaks matched exactly with the pure Cu-BTC, [29][30][31][32] and no additional peak of impurities was detected. The result of the XRD patterns suggests that pure Cu-BTC can be synthesized by sonochemical method within 1 min at room temperature and atmospheric pressure.…”
Section: Resultssupporting
confidence: 91%
“…There have been continuous efforts to improve the synthesis and activation of Cu-BTC. [30][31][32][33] Various MOFs have generally been synthesized widely by slow diffusion techniques, conventional hydrothermal and solvothermal methods. [1][2][3][4] However, the reactions used to synthesize many MOFs, particularly those with good thermal stability, require hydro/solvothermal synthesis conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, alternately immersing the SAM/Au substrates in separate metal and linker solutions, with solvent washing steps in between, assures controlled growth. Resulting SURMOF orientation is dictated by the terminating groups of the SAMs 14, 18, 19. The most studied example of a SURMOF is [Cu 3 (btc) 2 (H 2 O) n ], commonly known as HKUST‐1, which typically includes copper acetate (Cu(CH 3 COO) 2 , abbreviated here as CuAc 2 ) and 1,3,5‐benzenetricarboxylate (btc) as precursors 8, 20…”
Section: Introductionmentioning
confidence: 99%
“…for the Cu 2 (F 4 bdc) 2 ‐(dabco) SURMOF (dabco=1,4‐diazabicyclo[2.2.2]octane), but so far no conclusive results have been found for HKUST‐1 14. Therefore, fundamental understanding, and as a result further synthetic improvements, are needed in order to justify advantages of the LbL approach over other synthetic strategies 19, 24, 25, 26, 27…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recently, intensive studies have been reported towards MOF thin films with liquid phase epitaxy (LPE) and integration of LangmuirBlodgett film method with LPE, to control growth orientation, thickness, and morphology without losing bulk phase properties on oxide substrates, semiconductors, and self-assembled monolayers (SAMs). [4][5][6][7][8] However, these challenges have not been extended to an optically transparent semiconductor such as TiO 2 , ITO and FTO etc.…”
Section: Introductionmentioning
confidence: 99%